Financial accounting and reporting 1 - Ahmad, Azlina; Mohd Saat, Nur Ashikin; Mahmud, Radziah; Mohd Aripin, Rosmini; Ngalim, Siti Manisah; Abd Talib, Maswati; Abdullah, Asna Atqa (Oxford University Press, 2015)
This textbook is intended to be used as reference for the introductory level financial accounting and reporting course. Its emphasis is on awareness of IFRS judgements and estimates, in line with Stage 1 of the framework-based teaching. Accordingly, discussions in the chapters focus mostly on elements definition, recognition and initial measurement. Students are first given an overview of the Malaysian Financial Reporting Framework, followed by the introduction of the Conceptual Framework for Financial Reporting and an overview of the presentation of financial statements. Much of the explanatory material have been drawn from the Malaysian business setting. Key Features? The content complies with the latest Malaysian Financial Reporting Standards (MFRS) and is tailored for the financial accounting and reporting syllabuses of local universities. Review Questions and Application Exercises are provided at the end of each chapter to help students prepare for final examinations.? Check Your Understanding and Conceptual Framework Highlights are features built within the chapters to enhance the student’s learning process. Numerous examples with worked solutions are given to help students grasp important concepts.